Mitochondria-associated non-coding RNAs and their impact on drug resistance - An, Xingna; Sun, Lina; Zheng, Huan; Xiao, Yinghui; Sun, Weixia; Yu, Dehai (Frontiers in Pharmacology, 2025)
Drug resistance is a prevalent challenge in clinical disease treatment, often leading to disease relapse and poor prognosis. Therefore, it is crucial to gain a deeper understanding of the molecular mechanisms underlying drug resistance and to develop targeted strategies for its effective prevention and management. Mitochondria, as vital energy-producing organelles within cells, have been recognized as key regulators of drug sensitivity. Processes such as mitochondrial fission, fusion, mitophagy, changes in membrane potential, reactive oxygen species (ROS) accumulation, and oxidative phosphorylation (OXPHOS) are all linked to drug sensitivity. Non-coding RNAs (ncRNAs) enriched in mitochondria (mtncRNA), whether transcribed from mitochondrial DNA (mtDNA) or from the nucleus and transported to mitochondria, can regulate the transcription and translation of mtDNA, thus influencing mitochondrial function, including mitochondrial substance exchange and energy metabolism. This, in turn, directly or indirectly affects cellular sensitivity to drugs. This review summarizes the types of mtncRNAs associated with drug resistance and the molecular mechanisms regulating drug resistance. Our aim is to provide insights and strategies for overcoming drug resistance by modulating mtncRNAs.